Acute Aerobic Exercise Increases Cortical Activity during Working Memory: A Functional MRI Study in Female College Students - Li, Lin; Men, Wei-Wei; Chang, Yu-Kai; Fan, Ming-Xia; Ji, Liu; Wei, Gao-Xia (PLOS ONE, 2014)
There is increasing evidence that acute aerobic exercise is associated with improved cognitive function. However, neural correlates of its cognitive plasticity remain largely unknown. The present study examined the effect of a session of acute aerobic exercise on working memory task-evoked brain activity as well as task performance. A within-subjects design with a counterbalanced order was employed. Fifteen young female participants (M = 19.56, SD = 0.81) were scanned using functional magnetic resonance imaging while performing a working memory task, the N-back task, both following an acute exercise session with 20 minutes of moderate intensity and a control rest session. Although an acute session of exercise did not improve behavioral performance, we observed that it had a significant impact on brain activity during the 2-back condition of the N-back task. Specifically, acute exercise induced increased brain activation in the right middle prefrontal gyrus, the right lingual gyrus, and the left fusiform gyrus as well as deactivations in the anterior cingulate cortexes, the left inferior frontal gyrus, and the right paracentral lobule. Despite the lack of an effect on behavioral measures, significant changes after acute exercise with activation of the prefrontal and occipital cortexes and deactivation of the anterior cingulate cortexes and left frontal hemisphere reflect the improvement of executive control processes, indicating that acute exercise could benefit working memory at a macro-neural level. In addition to its effects on reversing recent obesity and disease trends, our results provide substantial evidence highlighting the importance of promoting physical activity across the lifespan to prevent or reverse cognitive and neural decline.